STUDY ON PERFORMANCE OF KENAF FIBRE/EPOXY REINFORCED ALUMINIUM LAMINATES (KeRALL) VIA COMPRESSION MOULDING TECHNIQUE - Edynoor, O.; Warikh, A.R.M.; Yahaya, S.H.; Salleh, M.S.; Moriga, T. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Fibre metal laminates (FML) technology is the best practice for wider usage of natural fibre. It could offer many superior mechanical properties because of the incorporating of metal elements. Therefore, the study is to reveal the findings of kenaf fibre/epoxy reinforced aluminium laminates (KeRALL) through the compression method. In this study, the temperatures of 27 °C and 80 °C were applied for the compression method. It was found that KeRALL WC yields higher Tg than KeRALL CC based on the DSC analysis. The KeRALL WC showed the highest flexural strength and better impact resistance as compared to KeRALL CC. For water absorption, KeRALL WC absorbed less water absorbed compared to KeRALL WC. For thermal expansion, the trend of the coefficient of thermal expansion (CTE) for KeRALL WC almost equal to the Al sheet with approximately 21% differences. Meanwhile, CTE for KeRALL CC was slightly different from the Al sheet and KeRALL WC. Finally, the fractographic image showed that the KeRALL WC sample had better interfacial bonding between composite (kenaf and epoxy) and Al sheet compared to the KeRALL CC. It was suggested that better bonding affects the overall properties of KeRALL. The empirical evidence presented in the results shows that KeRALL WC has the potential to be commercialized.